Reliability and radiation effects in compound semiconductors - Johnston, Allan (World Scientific, 2010)
This book focuses on reliability and radiation effects in compound semiconductors, which have evolved rapidly during the last 15 years. It starts with first principles, and shows how advances in device design and manufacturing have suppressed many of the older reliability mechanisms. It is the first book that comprehensively covers reliability and radiation effects in optoelectronic as well as microelectronic devices. It contrasts reliability mechanisms of compound semiconductors with those of silicon-based devices, and shows that the reliability of many compound semiconductors has improved to the level where they can be used for ten years or more with low failure rates.